METODE TAFSIR TAHLILI DAN MAUDHU’I - hemlan elhany (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2018)
The Qur'an is the Arabic language book which was revealed by Allah SWT to His Messenger Muhammmad SAW, as guidance and mercy in all aspects of human life. The Qur'an contains information about past, present and future events, worldly. In addition, the Qur'an contains the laws governing human relationships with Allah SWT, among human beings with their natural environment. To explore and uncover the contents of the Qur'an, it is necessary to understand and uncover the contents and the principles it contains. That ability and understanding is necessary in the interpretation of the verses of the Qur'an. Therefore it is said that: the interpretation is the key to opening a storage warehouse buried in the Qur'an, without the interpretation of people will not open the warehouse to get the pearls and gems therein. The tahlili interpretation method is the method of interpretation of verses Al-qur'an by describing the description of eating in the verses of al-qur'an and conducting analysis. The interpretation method of tahlili, the mufasirnya tried to explain the contents of the Qur'anic verse from various points, and pay attention to the sequence of the verses of the Qur'an, starting with the letter Al-Fatihah, Al-Baqarah, Ali Imran, and so on. -nas. The method of tafsir maudhu'I, is an explanation of things; which deals with one of several themes of life of thought, social, culture, justice, nature, and others from the perspective of the Qur'an.